2016
DOI: 10.1021/acs.jpcb.6b08678
|View full text |Cite
|
Sign up to set email alerts
|

Refining Disordered Peptide Ensembles with Computational Amide I Spectroscopy: Application to Elastin-Like Peptides

Abstract: The characterization of intrinsically disordered protein (IDP) ensembles is complicated both by inherent heterogeneity and by the fact that many common experimental techniques function poorly when applied to IDPs. For this reason, the development of alternative structural tools for probing IDP ensembles has attracted considerable attention. Here we describe our recent work in developing experimental and computational tools for characterizing IDP ensembles using Amide I (backbone carbonyl stretch) vibrational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Our objective in this study is to test an ensemble refinement scheme that can be used to account for complex spectral features such as those found in FTIR and 2D IR spectra. In our recent study of ELPs, the ME refinement is proved effective for describing the extension in a type-I turn across multiple FFs (5). However, the constraints of mean frequency and variance of a spectrally isolated peak is not easily extended to more complex features such as multiple overlapping resonances and asymmetric spectral line shapes.…”
Section: Ensemble Refinement Against Amide I Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…Our objective in this study is to test an ensemble refinement scheme that can be used to account for complex spectral features such as those found in FTIR and 2D IR spectra. In our recent study of ELPs, the ME refinement is proved effective for describing the extension in a type-I turn across multiple FFs (5). However, the constraints of mean frequency and variance of a spectrally isolated peak is not easily extended to more complex features such as multiple overlapping resonances and asymmetric spectral line shapes.…”
Section: Ensemble Refinement Against Amide I Spectroscopymentioning
confidence: 99%
“…Among these factors, we found that the most significant factor is the error due to the frequency map, as partly seen in the systematic bias present in different water models above. Taking 2s (54 cm À1 ) of the spectroscopic map error as the estimated confidence interval (5,53), the highest uncertainty of determining the ensemble populations against the full set of spectra is found to be 18% in AMBERfb15 ensembles (Table S4). These high uncertainties indicate that the frequency error is the most influential source of degrading quality of the ensemble refinement.…”
Section: Errors In Spectroscopic Mapsmentioning
confidence: 99%
See 3 more Smart Citations